Hydrolysable tannins, physicochemical properties, and antioxidant property of wild-harvested Terminalia ferdinandiana (exell) fruit at different maturity stages - Phan, Anh Dao Thi; Zhang, Jiale; Seididamyeh, Maral; Srivarathan, Sukirtha; Netzel, Michael E.; Sivakumar, Dharini; Sultanbawa, Yasmina (Frontiers in Nutrition, 2022)
Terminalia ferdinandiana Exell., also known as Kakadu plum, is a wild-harvested native Australian fruit with limited information on how maturity is affecting the phytonutritional properties and bioactivities of the fruit. Thus, the present study investigated changes in hydrolysable tannins, phenolic acids, sugar profile, standard physico-chemical parameters and antioxidant scavenging capacity of wild-harvested Kakadu plum fruits at four different maturity stages, from immature to fully mature. Fruits harvested less than 25, 25-50, 50-75 and 75-100% degree of fullness were classified as highly immature (stage 1), immature (stage 2), semi-mature (stage 3), and fully mature (stage 4), respectively. Results showed that chebulagic acid, geraniin, chebulinic acid, castalagin, punicalagin and gallic acid continuously decreased during fruit maturity, while elaeocarpusin, helioscopin B, corilagin, 3,4,6-tri-O-galloyl-S-glucose and ellagic acid increased at the beginning of fruit growth (from stage 1 to 2), but decreased when the fruits reached their full maturity (stage 4). The levels of hydrolysable tannins and phenolic acids in fully mature fruits (stage 4) was significantly (p≤0.05) lower than that in their immature counterparts (stage 1 and 2). Total phenolic content (TPC) and DPPH antioxidant radical scavenging activity did not vary significantly between different maturity stages. Pearson’s correlation coefficient test indicated that TPC and DPPH positively (p≤0.05) correlate with most of the studied tannin compounds. Sugars (glucose, fructose, and sucrose), total soluble solid content and titratable acidity increased during the fruit development. Furthermore, principal component analysis (PCA) revealed the difference between the immature and mature samples, based on their nutritional profile and bioactive compounds. The PCA results also suggested a considerable variability between the individual trees, highlighting the challenges of wild harvest practice.